DESAIN ORGANISASI PEMBELAJARAN, KEPUASAN, DAN KINERJA MELALUI KESEJAHTERAAN, INOVASI, DAN KOMITMEN GURU ASN DAN NON-ASN: STUDI PADA SEKOLAH MENENGAH DI KOTA JAMBI (PENDEKATAN STRUCTURAL EQUATION MODELING) - Hansein Arif Wijaya; Robi Hendra; Muhammad Fauzan; Dian Arisandy Eka Putra Sembiring (Jurnal Manajemen Pendidikan, 2026)
This study examines the impact of organizational learning design on teacher performance and job satisfaction in secondary schools, focusing on well-being, innovation, and commitment as mediating factors. Using a quantitative survey method, data were collected from 367 S1-certified teachers in Jambi City, Indonesia. The survey included 54 items adapted from established scales related to organizational learning, teacher satisfaction, commitment, innovation, performance, and well-being. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that organizational learning design significantly influences teacher commitment and well-being, both of which positively affect job satisfaction and performance. However, the effect of innovation on performance was non-significant, suggesting a need for more targeted strategies to integrate innovation into teaching practices. These results emphasize the importance of a supportive organizational learning environment to enhance teacher engagement and effectiveness. Recommendations are offered for educational policymakers to bolster teacher well-being and commitment through organizational learning initiatives.